The Impact of Harsh Parenting on the Development of Obesity in Adulthood: An Examination of Epigenetic/Gene Expression Mediators Among African American Youth - Lei, Man-Kit; Beach, Steven R. H.; Simons, Ronald L.; Ye, Kaixiong (Frontiers in Cardiovascular Medicine, 2021)
Objective: We examined the association of prospectively assessed harsh parenting during adolescence with body mass index (BMI) in young adulthood among African American youth. We also assessed the role of methylation of obesity-related genes and gene expression markers of obesity as mediators of this association, providing a pathway for the biological embedding of early harsh parenting and its long-term impact on young adult health. Methods: Hypotheses were tested with a sample of 362 African American youth for whom harsh parenting was assessed at ages 10–15, BMI was assessed at age 10 and 29, and both DNA methylation (DNAm) and gene expression of obesity genes were assessed at age 29. Mediational analyses were conducted using bootstrap methods to generate confidence intervals. Results: Controlling for genetic risk for obesity and health-related covariates, harsh parenting across childhood and adolescence was associated with change in BMI (Δ BMI) from ages 10–29. In addition, we found that the indirect effect of harsh parenting on Δ BMI was mediated through obesity-related DNAm and accounted for 45.3% of the total effect. Further, obesity-related DNAm mediated the effect of harsh parenting on gene expression of obesity-related genes (GEOG), and GEOG, in turn, mediated the impact of obesity-related DNAm on ΔBMI. This pathway accounted for 3.4% of the total effect. There were no gender differences in the magnitude of this indirect effect. Conclusions: The results suggest that alterations in methylation and gene expression mediate the impact of harsh parenting on change in obesity from childhood to young adulthood, illustrating plausible biological pathways from harsh parenting to obesity and bolstering the hypothesis that harsh parenting in childhood and adolescence can become biologically embedded and contribute to obesity.